PRINCIPLES OF TEACHING HUMAN ANATOMY FOR MEDICAL STUDENTS MAJORING IN 228 "PEDIATRICS" - Miskiv, V. A.; Popadynets, O. G.; Kulynych-Miskiv, M. O.; Bodnarchuk, Yu. V.; Dutchak, U. M.; Knyazevich-Chorna, T. V.; Oliynyk, R. P.; Khabchuk, V. S.; Grechin, A. B.; Pertsovych, V. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2022)
The work is devoted to the methodological features of the study of human anatomy by pediatric students. The experience of the department in teaching human anatomy in the light of the "Strategy for the development of medical education", taking into account the content of educational programs and current trends in digitalization of higher education in general and medicine in particular. The experience of application of interdisciplinary integration of curricula, accompanied by increasing the effectiveness of training of future pediatricians by giving practical lectures together with leading experts in propaedeutics of pediatrics, which allows as close as possible to modern requirements of the educational environment. And the use of computer testing has a training section that helps to master the material passed, and through the use of graphical tests, contributes to the visual formation of chains of interconnected processes. The issue of optimization of the educational process in medical educational institutions is relevant for the training of highly qualified personnel. In view of the above, classes with pediatric students require special attention of teachers of the department to ensure optimal conditions for the educational process using educational materials, visual aids, computer teaching aids, which allows to structure the student’s cognitive activity to acquire the necessary in further knowledge and skills.